Utilization of Satellite Imagery and Integration of the HVSR Inversion Method for Coastline Changes in the Nangai Beach Tourism Area, North Bengkulu Regency - Helinnes, Putri; Hadi, Arif Ismul; Farid, Muchammad; Setyowati, Yuni; Hardiansa, Debi; Gumanty, Usman; Raihana, Hana; Al-Ansory, Andre Rahmat; Muammar, Zaky (Universitas Diponegoro, 2025)
This research analyzes shoreline changes in the Nangai Beach area; North Bengkulu Regency using Satellite Image data and analyzes subsurface structures using the Horizontal to Vertical Spectral Ratio (HVSR) method. The main objective of this research is to identify shoreline changes along the Nangai Beach area that occur due to abrasion. Data were collected from 30 points, with a distance of ±100 meters between each point. The research shows that the condition of the area is quite stable to vulnerable to the occurrence of abrasion disasters. Coastline changes were obtained using Satellite Image data from 2011 to 2023. Changes can be observed between points 17 and 35.63 meters, and at point 2, 33.87 meters. The Horizontal-to-Vertical Spectral Ratio (HVSR) method determines dominant frequency values and processes them through amplification to calculate the seismic vulnerability index, sediment layer thickness, and shear wave speed. These values are used to identify areas vulnerable to coastal abrasion. Based on the interpretation, hard rock is shown with a dominant frequency value () in the range 2.35-5.08 Hz, while soft rock is shown in the range 5.71-9.05 Hz. The earthquake vulnerability value () in the range 0.49-2.68 is soft rock, while the value range 3.42-5.61 is hard rock. The lower the vulnerability value (), the more susceptible the area is to abrasion. The shear wave velocity () value is low with a range of 186.83-350.85 while the high value is with a range of 350.85-596.87. A layer of rock with a 3D cross-section can be viewed using 3D modeling software by entering the value of Vs. This research makes a significant contribution to abrasion disaster mitigation through a geophysical approach.